BIMBINGAN DAN KONSELING ISLAM DALAM MEMBENTUK SELF-EMPOWERMENT MAHASISWA BIMBINGAN DAN PENYULUHAN ISLAM UNIVERSITAS MUHAMMADIYAH PAREPARE - Dwi Susanto, Junaedi; Rezky, Ria (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2021)
The development of therapeutic sciense is currently growing rapidly, various treatment are used to overcome problems of self-development. Guidance and Counseling Islam is an Islamic Therapeutic path with the type of Islamic Counseling services as a therapeutic technique. In this study using Guidance and Counseling Islam in forming student self-empowerment through group counseling. The purpose of this study was to determine the effectiveness of Islamic Counseling in forming student self-empowerment. The research method used is the one group pretest-posttest experiment. With the result of research on the formation of significant self-empowerment in student after the group counseling process with Islamic counseling techniques, this formation is shown at a minimum pretest score of 164.00 and a maximum score of 185.00 with a standard rating of 0.05. these results indicated that the effectiveness of Islamic Counseling techniques in establishing successful student self-empowerment.